Much Ado about Nothing: Steele v Serepisos and a Notice Requirement for Contingent Conditions - Leslie, Sarah (Victoria University of Wellington Law Review, 2008)
In the 2006 case of Steele v Serepisos, the Supreme Court had an opportunity to clarify the law on contingent conditions. The issue was whether a party seeking to cancel a contract for its failure to fulfil a contingent condition first had to give notice to the other party. The purpose of the notice would be to give the other party an opportunity to fulfil the condition. A majority held, correctly in the author's view, that such a notice was not required. However, the majority went to some lengths to distinguish Cooke J's judgment in the 1978 case of Hunt v Wilson. This paper revisits Hunt v Wilson and argues that Cooke J's judgment was wrong. It further argues that the majority's failure to recognise this, coupled with general judicial confusion with respect to contingent conditions, made a simple issue much more difficult than it need have been.